2024
DOI: 10.1037/amp0001165
|View full text |Cite
|
Sign up to set email alerts
|

How subjective idea valuation energizes and guides creative idea generation.

Abstract: What drives us to search for creative ideas, and why does it feel good to find one? While previous studies demonstrated the positive influence of motivation on creative abilities, how reward and subjective values play a role in creativity remains unknown. This study proposes to characterize the role of individual preferences (how people value ideas) in creative ideation via behavioral experiments and computational modeling. Using the Free Generation of Associates Task coupled with rating tasks, we demonstrate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 84 publications
3
7
0
Order By: Relevance
“…This finding replicates Lopez-Persem et al (19) and suggests, together with other studies, that the evaluation step is essential in the creative process. For instance, previous results showed that an overly stringent evaluation inhibited creativity (26,71).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This finding replicates Lopez-Persem et al (19) and suggests, together with other studies, that the evaluation step is essential in the creative process. For instance, previous results showed that an overly stringent evaluation inhibited creativity (26,71).…”
Section: Discussionsupporting
confidence: 91%
“…The present study not only shows that individuals combine the dimensions of originality and adequacy into a subjective value, but it also demonstrates that the way they combine them (as estimated by the α and δ parameters of the CES model) relates to their creative abilities: giving more weight to an idea's originality over its adequacy (i.e., having a high α) and preferring a trade-off of these two dimensions rather than an extreme of either (i.e., having a low δ) correlated with higher scores in creativity tests. This finding replicates Lopez-Persem et al (19) and suggests, together with other studies, that the evaluation step is essential in the creative process. For instance, previous results showed that an overly stringent evaluation inhibited creativity (26,71).…”
Section: The Link Between Idea Valuation and Creative Abilitiessupporting
confidence: 90%
See 3 more Smart Citations